Health benefits for pregnant women followed by nurse-midwives versus family doctors - Germano Couto; Carolina Ferreira; Isabel Oliveira (Instituto Politécnico de Viseu, 2022)
Introduction: Pregnancy is a time of great emotions and new challenges that all women go through differently. Women choose different health care professionals to monitor their pregnancy. Therefore, it is essential to explore the benefits of monitoring the pregnancy by a nurse-midwife, promoting adherence to this follow-up model. Objective: To identify the benefits of monitoring pregnancy by nurse-midwives compared with family doctors. Methods: Integrative literature review in which six articles were included and thoroughly analyzed to respond to the outlined objective. The initial search covered the period from 2015 to 2021 and used the keywords 'Prenatal care', 'nurse-midwives', and 'childbirth'. 393 articles were retrieved and reduced to six considering inclusion criteria. The integrative review was descriptive and focused on extracting the findings that answered the research question. Results: Several benefits of monitoring pregnancy by a nurse-midwife compared to the same monitoring by a family doctor have been identified were identified: a decrease in the rate of cesarean sections, an increase in spontaneous vaginal births, a reduction in premature births, a reduction in interventions performed during childbirth, and an improvement in the emotional health of pregnant women. Conclusion: These results identify the potential benefits of physiological pregnancy monitoring by obstetric nurses compared with family physicians, which can help pregnant women make an informed and conscious decision about following their pregnancy, taking into account the gains for their health and their newborn. Health managers can also use these results to improve human resource management.